2008
DOI: 10.1111/j.1748-720x.2008.00261.x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Competencies for Public Health Emergency Legal Preparedness

Abstract: This paper is one of the four interrelated action agenda papers resulting from the National Summit on Public Health Legal Preparedness (Summit) convened in June 2007 by the Centers for Disease Control and Prevention, and multi-disciplinary partners. Each of the action agenda papers deals with one of the four core elements of legal preparedness: laws and legal authorities; competency in using those laws; and coordination of law-based public health actions; and information.This action agenda offers options for c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 4 publications
1
7
0
Order By: Relevance
“…This would be facilitated by familiarity with professional ethics as well as rules and regulations. 18 In the face of the many challenges in a disaster situation, it is crucial to have clear guidelines for nurses to allow them to follow ethical principles. 19 In addition, post-incident debriefing and a review of nurses' experiences are recommended to reinforce their development in applying ethical principles to their practice successfully.…”
Section: Discussionmentioning
confidence: 99%
“…This would be facilitated by familiarity with professional ethics as well as rules and regulations. 18 In the face of the many challenges in a disaster situation, it is crucial to have clear guidelines for nurses to allow them to follow ethical principles. 19 In addition, post-incident debriefing and a review of nurses' experiences are recommended to reinforce their development in applying ethical principles to their practice successfully.…”
Section: Discussionmentioning
confidence: 99%
“…Such networks would be overseen by a scientific research incident commander to coordinate the work. Gebbie, et al (2008) proposed more collaboration between practitioners and academics to further understanding of public health legal competencies, as well as including the competencies in law enforcement and judicial training programs and creating communities of practice, both vertically and horizontally, to develop specific practices for specific communities and events. Gray (1996) found that one factor which frequently generates conflict within collaborative organizations is control over resources and, on the other hand, a number of scholars have cited resource availability as a key factor in collaboration success (Provan and Milward, 1995;Rainey andBusson, 2001, as cited in Kiefer andMontjoy, 2006).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Perhaps the largest deficit in the existing research on the role of law in public health agency performance is its thin conception of legal capacity. There is a small literature that defines “legal competencies” (Center for Law and the Public's Health 2001; Gebbie et al 2008; Lichtveld et al 2002), but the field has not yet drawn on the theoretically richer sociolegal literature on the “legal consciousness” and the “legality” of individuals and organizations (Cooper 1995; Ewick and Silbey 1998; Silbey 2005; Stryker 2012). In this approach, law is not treated simply as a “tool” or “rule” that agents wield or obey but also as a set of individual beliefs and organizational norms regarding what the legal system is, how it actually works, and whether and why people should obey its commands.…”
Section: Integrating Phlr and Phssrmentioning
confidence: 99%